Outlander. Season 1, volume 1. [videorecording (DVD)] - Heughan, Sam, 1980-; Balfe, Caitriona; McTavish, Graham; Gabaldon, Diana (Sony Pictures Home Entertainment Inc., 2015)
Claire Randall is a married combat nurse from 1945 who is mysteriously swept back in time to 1743. She is immediately thrown into an unknown world where her life is threatened. When she is forced to marry a chivalrous and romantic young Scottish warrior, a passionate affair is ignited that tears Claire's heart between two vastly different men in two irreconcilable lives.